INTERDEPENDENCE OF THE CONCEPTS OF "HUMAN CASTLE" AND "HUMAN FACTOR" - Maikova , T. V.; Matvienko, A. G. (Problems of Informatization and Management, 2021)
The general issues of formation of human capital and its influence on the human factor, which has a place in the performance of certain functions of different nature with the participation of man, are insufficiently covered in the scientific literature.